Mindfulness w pracy z dziećmi i młodzieżą - Klon , Weronika; Waszyńska , Katarzyna (Studia Edukacyjne, 2020)
The article addresses the assumptions of mindfulness in children training. It contains clues to the use of some techniques in different age groups. It shows what benefits of both teachers and students in Polish school from implement mindfulness in the school curriculum. These effects pertain to the education process and social functioning. The article moreover contains a description of limitations in the realization of mindfulness assumptions in the Polish education system.